An ionospheric model for the arctic - Gassmann, George J.; Air Force Cambridge Research Laboratories (U.S.)
A first order approximation model of the Arctic ionosphere is described, based on published observations and concepts. The model allows for modifications and additions whenever new information becomes available, and will eventually represent a true picture available in real time or even as forecast. The location of the phenomena is specified in corrected geomagnetic latitude and local time. Various input parameters are included whenever some of their influences are known, such as UT, seasons, sunspot number, magnetic variations. The Arctic ionospheric features are specified as 'quasi-instant' deviations from routine predictions whereby the devitations represent probabilities of occurrence during periods that may range from 20 min to 3 hr. The following ionospheric features are more or less covered: auroral E (or night-E), auroral Es (or Esr), HF absorption, Arctic F. Necessary improvements to the model are indicated, including the inclusion of storm-time of individual substorms and the requirement that routine observations be maintained in the midnight sector of the auroral oval. (Author). Research supported by the Air Force Cambridge Research Laboratories, Office of Aerospace Research, United States Air Force, L.G. Hanscom Field, Bedford, Massachusetts. Ionospheric Physics Laboratory Project 5631. AD0715893 (from http://www.dtic.mil). "9 October 1970." Includes bibliographical references (page 9). A first order approximation model of the Arctic ionosphere is described, based on published observations and concepts. The model allows for modifications and additions whenever new information becomes available, and will eventually represent a true picture available in real time or even as forecast. The location of the phenomena is specified in corrected geomagnetic latitude and local time. Various input parameters are included whenever some of their influences are known, such as UT, seasons, sunspot number, magnetic variations. The Arctic ionospheric features are specified as 'quasi-instant' deviations from routine predictions whereby the devitations represent probabilities of occurrence during periods that may range from 20 min to 3 hr. The following ionospheric features are more or less covered: auroral E (or night-E), auroral Es (or Esr), HF absorption, Arctic F. Necessary improvements to the model are indicated, including the inclusion of storm-time of individual substorms and the requirement that routine observations be maintained in the midnight sector of the auroral oval. (Author). Mode of access: Internet.